Digital empathy and supply chain cybersecurity challenges: concept, framework and solutions for small-medium enterprises - Gani, Anisha Banu Dawood; Fernando, Yudi (Inderscience Enterprises Ltd., 2022)
Despite contributing significantly to the world’s economy and being the most targeted by cybercriminals for being the weakest link in the supply chain, small-medium enterprises (SMEs) lag behind cybersecurity implementation. The budget and expertise constraint hinders them from catching up with cybersecurity initiatives. This study explores the management concept of digital empathy and proposes a solution framework for SMEs to overcome cybersecurity challenges. We found that three drivers can be the solution to overcome the cybersecurity barrier within firms’ internal context, such as adequate funding, management support, and attitude towards cybersecurity risk. Our theoretical framework has also included the digital empathy approach incorporating subscription-based solutions, modular solutions, and zero-trust architecture. In addition, we suggest that the supply chain’s cybersecurity systems be regularly monitored and maintained to balance cybersecurity and affordability. Furthermore, to enable future scalability, SMEs must implement the zero-trust architecture, which acts as a foundation for self-healing and self-correcting supply chain networks.